An Update on Unloading Knee Braces in the Treatment of Unicompartmental Knee Osteoarthritis from the Last 10 Years: A Literature Review - Mistry, Dylan A.; Chandratreya, Amit; Lee, Paul Y. F. (The Surgery Journal, 2018)
Background The incidence of osteoarthritis is increasing and it is one of the most common causes of chronic conditions. Total knee replacement is the mainstay of treatment for end-stage knee osteoarthritis; however, with long waiting lists and high levels of dissatisfaction, a treatment like knee braces could potentially delay surgery. Unicompartmental knee osteoarthritis is associated with misalignment of the knee, and unloader bracing has been recommended by various guidelines to correct this misalignment. The aim of this report was to provide an update of evidence from the past 10 years on knee braces.Methods MEDLINE/EMBASE search was performed from the past 10 years.Results We reviewed the evidence from 14 published articles. Almost all articles supported knee brace use and showed it to decrease pain, improve function, and improve the quality of life of patients. One study in 2017 followed patients for long term and found knee bracing to be more cost effective than total knee replacement, and could replace the need for surgery. Several minor complications were reported with bracing, like soft tissue irritation, which could be due to poor fitting. A management strategy for this could be regular follow-up at a nurse-led clinic.Conclusions Unloader braces are an economical and effective treatment for unicompartmental knee osteoarthritis. They can significantly improve a patient's quality of life and potentially delay the need for surgery. Patients should be managed with a multidisciplinary approach with conservative management and knee bracing, before surgery is considered.
Keywords: knee osteoarthritis; braces; walking; knee arthroplasty; varus; valgus